Linguo-Cultural Competence Formation During the University Courses Learning; Advances in Intelligent Systems and Computing; Vol. 677 : Linguistic and Cultural Studies: Traditions and Innovations, (LKTI 2017) - Cheremisina Harrer I. A. Inna Aleksandrovna; Rostovtseva V. M. Veronika Mikhailovna; Kachalov N. A. Nikolay Aleksandrovich; Shcherbina Yu. V. Yunona (Language Teaching and Learning, 2017)
Title screen